Classification of research and development organizations by sector for assessment: case of materials science in Vietnam - Thao, Pham Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The research and development (R&D) system in Vietnam consists of diversified large number of institutions and it is impossible to evaluate the system as a whole at the same time in the current context. So assessment by subgroups of R&D institutions in the system may be a more feasible option. On the other hand, as the nature of assessment was to make comparison, so grouping by field of study may facilitate, at a certain level, the comparison. Furthermore, the results of assessment on a group of R&D in sector can help managers have clearer picture of R&D development of a field, for better service for S&T policymaking. To better understand about clustering method, this article analysed, as a case study, the R&D groups in the field of materials science. Materials Science is a field of interdisciplinary research which has received lot of attention of scientists community and research managers in recent years, it has become one of the most exciting research areas in Vietnam. By the method of data analysis and consultation with experts, the author of this article presents the concept, specialization of subjects under the study, and identify different types of R&D organizations R&D studying in Materials Science in Vietnam. Code: 15042301